Pedagogical tasks of forming the rules of perception of art works on the example of painting (Journal of Educational Sciences, 2023)
The necessity to foster a sense of beauty in a person, to foster creative thinking and abilities in youngsters and future instructors, determines the article's importance. The article discusses the findings of a study on how students at pedagogical universities specifically perceive works of fine art. The article's goal is to provide a summary of the approaches to pedagogical problems involving the development of skills for perceiving paintings. The study discusses the role that national art can play in the spiritual development of young people and defines strategies for incorporating it into educational settings. On the basis of analytical and synthetic methods, the general spiritual and moral approach to the organization of cognitive activity of the training youth; the authors of the article offer a description of the ways of perception and understanding of works of artistic creativity, while both content content and methodical support of the work are taken into account in the implementation of pedagogical tasks. In the study's practical component, 54 students from O.Zhanibekov South Kazakhstan Pedagogical University prepared an essay on the theme "Basic principle of perception of artistic text." The students completed a content analysis essay in which they analyzed the concepts that, in their opinion, are crucial to the perception of the image. The majority of students identified the principle "ethical principle" as the fundamental principle. The selection of the leading principles of visual art by future teachers is critical, because it determines what message students use to understand life through the language of art. The article was supported by the Ministry of Science and Higher Education  RK АР09259731 "Didactic potential of national painting in the implementation of the program of spiritual revival of the nation".Key words: psychology, artistic creativity, painting, spirituality formation, influence, perception, awareness.